32 Laboratory Evaluation for Therapy-Related Myeloid Neoplasia-Associated Changes After Autotransplant for Multiple Myeloma. (11th January 2018) - Guillory, Tesha; Almaula, Dhwani; Saxe, Debra; Nooka, Ajay; Jaye, David
Abstract: Therapy-related myeloid neoplasms (tMNs), especially MDS and AML, are well-known, serious complications of chemotherapy agents, such as topoisomerase II inhibitors and alkylating agents. It is less clear if newer efficacious agents such a lenalidomide (LEN) carry an increased risk of tMN. The overall incidence of tMNs in treated multiple myeloma (MM) patients is approximately 3%. Our laboratory evaluates a high volume of MM bone marrow (BM) biopsies with a full complement of ancillary studies, including many from patients that are post-autotransplant. To better understand the ordering pattern and utility of complex ancillary studies to detect tMN, we queried the departmental pathology database from May 2011 to December 2016 and found results for 1, 212 MM patients who received biopsies following autotransplantation. We identified patients that had MDS fluorescence in situ hybridization (FISH) abnormalities, myeloid-related karyotypic abnormalities, or abnormal myeloblasts by flow cytometry as indicators of possible tMN, excluding MM-associated changes. We found two of 14 patients had an abnormal MDS FISH panel result and a third had a borderline/equivocal result. Myeloid-related karyotype abnormalities were observed for 51/1, 208 patients and defined the same abnormalities for the two patients with abnormal MDS FISH. These karyotype abnormalities were grouped into risk categories (18% high risk, 2% intermediate risk, 47% low risk, 33% uncertain risk). Seven of 1, 212 patients displayed abnormal myeloblasts by flow cytometry, for which three patients also had an abnormal myeloid-related karyotype that fell into the high-risk group. A subset of these data was analyzed to test whether patients given LEN display increased tMN incidence. Three hundred ninety-seven patients received uniform pretransplant induction therapy with subsets receiving LEN-only maintenance or observation. No significant differences were found between groups concerning age, gender, ethnicity, Ig isotype, number of posttransplant marrow analyses, or average interval from transplant to last biopsy. Lab indicators of possible tMN for LEN-only (n = 13/271) and the observation group (3/92) were not statistically significant between groups ( P = .77). Our data suggest several interesting conclusions. First, tMN-associated findings are rare in our patient population and consistent with reported rates. Second, from a lab perspective, MDS FISH provides little added value over routine karyotyping in evaluation for tMN, arguing against the use of this expensive test in this clinical situation. Third, while some published data suggest a higher rate of second malignancies in patients' receiving LEN maintenance treatment, in our well-controlled subset analysis, LEN-only maintenance therapy does not yield significantly higher rates of tMN-associated lab findings.